Computed Tomography Screening for Lung Cancer: Mediastinal Lymph Node Resection in Stage IA Nonsmall Cell Lung Cancer Manifesting as Subsolid and Solid Nodules. Issue 5 (May 2017) - Flores, Raja M.; Nicastri, Daniel; Bauer, Thomas; Aye, Ralph; Andaz, Shahriyour; Kohman, Leslie; Sheppard, Barry; Mayfield, William; Thurer, Richard; Korst, Robert; Straznicka, Michaela; Grannis, Fred; et al.
Abstract : Objective: To compare long-term survival rates of patients with first, primary, clinical stage IA nonsmall cell lung cancer from a large cohort undergoing computed tomography screening with and without mediastinal lymph node resection (MLNR) under an Institutional Review Board-approved common protocol from 1992 to 2014. Background: Assessing survival differences of patients with and without MLNR manifesting as solid and subsolid nodules. Methods: Long-term Kaplan-Meier (K-M) survival rates for those with and without MLNR were compared and Cox regression analyses were used to adjust for demographic, computed tomography, and surgical covariates. Results: The long-term K-M rates for 462 with and 145 without MLNR was 92% versus 96% ( P = 0.19), respectively. For 203 patients with a subsolid nodule, 151 with and 52 without MLNR, the rate was 100%. For the 404 patients with a solid nodule, 311 with and 93 without MLNR, the rate was 87% versus 94% ( P = 0.24) and Cox regression showed no statistically significant difference ( P = 0.28) when adjusted for all covariates. Risk of dying increased significantly with increasing decades of age (hazard ratio [HR] 2.3, 95% confidence interval [CI] 1.4–3.8), centrally located tumor (HR 2.5, 95% CI 1.2–5.2), tumor size 21 to 30 mm (HR 2.7, 95% CI 1.2–6.0), and invasion beyond the lung stroma (HR 3.0, 95% CI 1.4–6.1). For the 346 patients with MLNR, tumor size was 20 mm or less; K-M rates for the 269 patients with and 169 patients without MLNR were also not significantly different (HR 2.1, P = 0.24). Conclusions: It is not mandatory to perform MLNR when screen-diagnosed nonsmall cell lung cancer manifests as a subsolid nodule.